Relação entre estratégias de crescimento, fotossíntese e uso de nitrogênio e fósforo por gramíneas forrageiras C4 nativas da América do Sul - Marques, Anderson Cesar Ramos (2017)
The aim of this thesis is to evaluate different species of native grasses from southern Brazil grasslands of contrasting in its specific leaf area (SLA) and leaf dry matter content (LDMC) traits, if species of higher SLA have greater assimilation of CO2, as well, its relation with leaf nitrogen (N) under natural fertility conditions and with N fertilizetion. In addition, a possible correlation between leaf and root attributes was tested. In order to determine if the species with contracting growth strategies are also contrasting in the concentration of P in the dry matter, relative growth rate (RGR), and to determine if the highest RGR is related to a higher capacity of P influx by plants, and with higher affinity transporters for P. In greenhouse studies, the thesis presents seven chapters. The first chapter is a review about factors that led to the formation of natural grasslands in South America, and the adaptive mechanisms of species to climate and soil conditions. The second chapter is about the relationship of leaf attributes, N concentration, CO2 assimilation and water use in photosynthesis was made with ten species and five replications, where the treatments were the species. The third chapter used eight species under conditions of natural fertility and N addition, was quantified the effect of fertilization with N on the photosynthesis and leaf area of the species. The fourth chapter, which has the same design as the second chapter, discusses the relationship between leaf and root attributes and brings a proposition of groups of species based on these attributes. The fifth chapter, which aimed to identify the effect of the variation of the availability of P on the consistency of the attributes of leaves and roots, was done with eight species and four replicates. The sixth chapter tested the relationship between the relative growth rate and the absorption capacity of P by two grasses with contrasting growth strategies. At the end, in the seventh chapter, the final considera-tions bring an approach about the correlation between the variables, with the proposed a conceptual model with the possible interactions. Our data indicates that the species of higher SLA and lower LDMC have a greater capacity of assimilation of CO2 and productivity of leaf N, as well as, they are species with greater ability to respond for leaf area to N fertilization, which leads to a higher rate of assimilation of CO2 with the use of fertilization. The pattern of dry matter (DM) allocation between shoot and root system presents the same pattern for the tested species, that is, species with larger leaf area per DM unit of leaves also produce larger surface area and root length per DM unit of root. In addition, the higher DM content of the leaves was positively correlated with the higher density of root tissue and greater root diameter. The species with higher RGR were characterized by the greater influx of P and by transporters of higher affinity, able to absorb P in lower con-centration in the soil.